COMPARATIVE STUDY OF OXIDATIVE STRESS MARKER MALONDIALDEHYDE ON DASAMOOLARISHTA AND ETHANOL TREATED HEALTHY WISTAR ALBINO RATS - Pandarekandy Seena, Thadathil; Subrahmanyan Surya, Padinjareveedu; Kannamparathazhathethil Sneha, Girijavallabhan; Rahmath, Abdulrahiman; Sreekumaran, Edakkot (International Journal of Ayurveda and Pharma Research, 2015)
Malondialdehyde (MDA) is an end product of lipid peroxidation, involved in several enzymatic and non enzymatic reactions. The present study compares the level of malondialdehyde on self generated alcoholic product Dasamoolarishta with the lab grade ethanol treated healthy rats. In this study, 18 Wistar albino male rats of the same age, littermates and body weight groups were used. Among these, six of each were grouped into Control (C), Dasamoolarishta treated (Test 1) and 6% Ethanol treated (Test 2) groups. Duration of this study was 30 days. Before starting the experiment, body weight and fasting blood glucose level was checked and verified that the animals were healthy. From the first day onwards the control group was orally treated with tap water (1 ml/kg body weight) and test groups were orally treated with Dasamoolarishta (1 ml/kg body weight) and ethanol treated (1 ml/kg body weight). At the end of the administration period, body weight and fasting blood glucose levels were taken and then the animals were sacrificed and the liver tissue was isolated. The Lipid peroxidation status of liver tissue of both control and test groups were analysed. Body weight, fasting blood glucose and lipid peroxidation (Malondialdehyde - MDA) level in liver tissues of both the groups were statistically analysed using ANOVA. Dasamoolarishta treated group showed reduced malondialdehyde level than ethanol treated group. It indicates that self generated alcohol in Dasamoolarishta does not have any ill effect, thereby showing a protective role in free radical scavenging.